Imagist, Visual and Emotional Elements in Ernest Hemingway’s Writing : Case Studies of the Reader’s Experience in “Hills Like White Elephants” and The Old Man and the Sea - Hellman, Anni (My University, 2022)
In this thesis, I examine two texts by Ernest Hemingway: a short story “Hills Like White Elephants” and the ending scene of famous short novel The Old Man and the Sea. The emphasis of this research is to find out the techniques of writing that make the writing on the paper to become a real-life experience and that create a memory in the reader’s mind. Hemingway’s famous iceberg theory, the idea that he states only the tip of the iceberg and by carefully chosen elements creates another dimension that looms below the surface and makes the reader experience “something more than they understood.” In order to reveal the secrets of the writing technique, I do not only research the iceberg theory and its links to the human unconscious, but I aim at researching elements that are relevant in the creation of the reading experience. I have categorized the elements to imagist features, to feelings and emotions and to visual dimensions. In addition, my research exemplifies that these elements follow Hemingway’s artistic career from the beginning to the end as “Hills Like White Elephants” was written in the early phase of Hemingway’s career, after his years in Paris and The Old man and the Sea in contrast is Hemingway’s last major work of art. As a methodology of analysis, I apply Louise Rosenblatt’s theory of aesthetic reading. It emphasizes the importance of the experience of reading and differentiates it from efferent reading, where the reader seeks information. This theory supports the aims that Hemingway had for his writing: to create a real-life experience to the reader.
Keywords: iceberg theory, reader-response criticism, aesthetic reading, Ernest Hemingway